Expression profile analysis of two cathepsin S in channel catfish (Ictalurus punctatus) mucosal tissues following bacterial challenge. (January 2016) - Dong, Xiaoyu; Ye, Zhi; Song, Lin; Su, Baofeng; Zhao, Honggang; Peatman, Eric; Li, Chao
Abstract: Cathepsin S belongs to the papain family of cysteine protease, and is considered to play key roles in immune responses after bacterial challenge. However, despite the recognized importance of Cathepsin S in immunity, no studies have systematically characterized Cathepsin S in catfish. In this regard, here, we characterized the Cathepsin S gene family in channel catfish, and investigated their expression patterns following two different Gram-negative bacterial challenge. In the present study, two Cathepsin S genes ( ctss and ctssa ) were captured in channel catfish. In comparison to other species, the catfish Cathepsin S genes are highly conserved in their structural features. Phylogenetic analysis indicated the strongest phylogenetic relationship with zebrafish, which is consistent with their evolutional relationships. Tissue distribution analysis revealed that Cathepsin S genes were ubiquitously expressed in catfish tissues. Following bacterial infection, the Cathepsin S genes were significantly up-regulated at most time-points in mucosal surfaces, with an acute response post Edwardsiella ictaluri infection. Obviously, the expression profiles were quite distinct between two Cathepsin S genes, across the tissues and between pathogens, suggesting that Cathepsin S genes may exert disparate roles in mucosal immune responses. Our findings here, provide early insight into the immune functions of Cathepsin S in catfish; however, further studies are needed to determine the mechanisms of Cathepsin S for antigen presentation during inflammatory processes and innate host defense. Highlights: Two Cathepsin S were identified in channel catfish. Cathepsin S were ubiquitously expressed in catfish tissues. Cathepsin S genes were significantly induced after bacterial challenge.